Islamic Guidance And Counseling As A Framework For Personal And Societal Well-Being In Islamic Societies - Abdullahi, Nazeer Datti (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
The increasing secularization of modern societies has challenged the integration of faith-based values in counseling, creating a gap between spiritual needs and psychological practices. This study aims to explore Islamic guidance and counseling as a holistic framework for addressing personal, educational, and social well-being in Islamic societies. Using a qualitative library-based method, the research analyzes classical Islamic texts, contemporary scholarly works, and recent studies on counseling and psychology. The findings reveal that Islamic counseling, rooted in the Qur’an and Sunnah, effectively promotes compassion, forgiveness, justice, and resilience, aligning closely with modern psychological principles of well-being. Moreover, it offers unique contributions to mental health, conflict resolution, and social justice through its integration of spiritual and ethical dimensions. This study contributes to the growing discourse on faith-based counseling by proposing an integrative model that harmonizes spiritual authenticity with professional psychological practice